Protective Effects of Hydroalcoholic Extract of Rosa canina Fruit on Vancomycin-Induced Nephrotoxicity in Rats. (28th May 2021) - Sadeghi, Hossein; Karimizadeh, Ehsan; Sadeghi, Heibatollah; Panahi kokhdan, Esmaeel; Mansourian, Mahboubeh; Abbaszadeh-Goudarzi, Kazem; Shokripour, Mansoureh; Asfaram, Arash; Doustimotlagh, Amir Hossein
Abstract : Vancomycin-induced nephrotoxicity (VIN) has been reported to occur in 5–35% of recipient patients. The aims of the study were to evaluate protective effects of Rosa canina (RC) on VIN in rats. Rats were randomly divided into five groups as follows: control group I, group II (received VAN 400 mg/kg/day, every 12 h at doses of 200 mg/kg/day, for 7 consecutive days), group III (VAN + RC 250 mg/kg/day, for 7 consecutive days), group IV (VAN + RC 500 mg/kg/day, for consecutive days), and group V (received RC 500 mg/kg/day, for consecutive 7 days). On the eighth day after anesthetizing the animals, blood samples were taken from the heart, and then, the kidneys were removed to investigate kidney function, oxidative stress, and histopathological marker. Also, the chemical composition of RC extract was identified by GC-MS analysis. Oral dose of 500 mg/kg RC extract significantly reduced the serum levels of blood urea nitrogen (BUN), creatinine (Cr), malondialdehyde (MDA), and nitric oxide (NO) and also the kidney tissue MDA, protein carbonyl, and NO metabolites (nitrite) levels compared to the VAN-treated group (P < 0.05 ). Based on histopathological analysis, RC extract at the dose of 500 mg/kg inhibited the destructive effects of VAN on kidney tissues. GC-MS analysis indicated that the main compositions were found to be lactose (21.96%), 3-t-butyloxaziridine (20.91%), and 5-oxymethylfurfurole (16.75%). The results indicated that oral administration of RC was able to reduce VAN-induced nephrotoxicity in rats, possibly through antioxidant pathways.